2020
DOI: 10.21580/at.v12i1.4515
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Pembelajaran dengan E-Modul Berbasis Kvisoft Flipbook Maker untuk Mata Kualiah Program Linier

Abstract: <div><table cellspacing="0" cellpadding="0" align="right"><tbody><tr><td align="left" valign="top"><p>This study aims to improve the independence of students in learning Linear Program by using e-module learning media linear program based on Kvisoft Flipbook Maker. This research is a Classroom Action Research (CAR). This research was conducted in the mathematics education study program FKIP UAD. The results of this study indicate an increase in student learning independence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The characteristic of e-modules is their small form, which makes them easier to use in small rooms. It is possible to store information on a flash drive or mobile phone and have access to it anywhere, and the module also has animations and simulations that can help students learn the material, as well as the opinion of Priwantoro et al (2018), Flipbook maker is software that is used to make a book display into a digital electronic book in the form of a flipbook.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of e-modules is their small form, which makes them easier to use in small rooms. It is possible to store information on a flash drive or mobile phone and have access to it anywhere, and the module also has animations and simulations that can help students learn the material, as well as the opinion of Priwantoro et al (2018), Flipbook maker is software that is used to make a book display into a digital electronic book in the form of a flipbook.…”
Section: Discussionmentioning
confidence: 99%
“…From this average, it can be concluded that e-modules with smart phone-based with realistic mathematic education are considered valid and practical. They can be used in the learning process with two-variable linear system material, and technology-based e-modules will positively respond to students (Priwantoro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang serupa tentang efektifitas penerapan modul virtual multimedia flipbook berbasis scientific approach terhadap hasil.belajar.kognitif dan persepsi.mahasiswa pada.matakuliah program linier menunjukkan bahwa dapat meningkatkan pemahaman dan kemandirian peserta didik dalam mempelajari konsep dan meningkatkan hasil kognitifnya (Priwantoro et al, 2020).…”
Section: Pendahuluanunclassified